In vitro evaluation of a ceramic bracket with a laser-structured base - Selma Elekdag-Türk (BMC, 2020)
Abstract Background The purpose of this study was the assessment of shear bond strength (SBS), adhesive remnant characteristics, integrity of the enamel, integrity of Discovery Pearl as well as the integrity of Fascination 2 ceramic brackets following SBS testing. Methods Sixty maxillary first premolars were randomly assigned into two groups. These groups were bonded with their respective brackets. The samples underwent thermocycling (1000 cycles), SBS testing and assessment of the residual adhesive. The statistical analyses used were the independent samples t-test, the Weibull analysis and the chi-square test. Results The independent samples t-test for the comparison of the mean SBS resulted in significant differences between Fascination 2 (10.50 ± 2.61 MPa) and Pearl (13.01 ± 2.50 MPa) brackets (p = 0.0003). The results of the chi-square test for ARI demonstrated a significant difference (p = 0.000) between the groups. A higher frequency of ARI scores of 2 and 3 for Pearl brackets existed. Enamel damage and bracket fracturing was not observed. Conclusions The mean bond strength value, the adhesive remnant characteristics, the integrity of the enamel and the ceramic brackets as well as the Weibull analyses outcomes were highly encouraging during this in vitro screening. The way is paved for an in vivo investigation with the Pearl ceramic bracket.